Assessment of GMP Compliance in Tempe Production on Sepande Village - Atika Permata Sari; Hamidah Hendrarini; Eko Nurhadi (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2024)
Food safety is an essential aspect of sanitation science. Food safety is an essential characteristic of life, both for food producers and consumers. Therefore, food processing enterprises must prioritize hygiene standards for the common good and maintain consumer confidence by improving food security assurances. The consumption of tempe by Indonesian people is relatively high because there is an advantage that tempe has in terms of nutritional value over other foods. The regulations of the Minister of Industry were issued by the Drug and Food Supervisory Authority (BPOM) 14 years ago, and the artisans should have already carried out the production process following the requirements of the regulations. The study aims to evaluate compliance with good manufacturing practices in Tempe production and analyze the correlation between compliance with good manufacturing practices and profits. The study was conducted in May 2024 in the village of Sepande. The number of respondents in this study is 50 tempe artisans, with the probability sampling techniques taking into account that Sepande Village is the area that has the most tempe industry homes and the highest tempe producer in the Candi district. The analysis method used in the first instance is the GMP assessment checklist form, then analyzed using the GAP Analysis method to analyze the gaps that occur, and in the second instance to analyze the costs and profits, then provide a list of questions with the Likert scale method, then correlated using the help of SPSS software with the Spearman Rank Test. The results show that based on the assessment of the aspects of Good Processed Food Production in Tempe products in the village of Sepande, the level of compliance has been applied following the regulations of the ministry as well as the benefits that influence the way good processed food is produced.